Application of long non-coding RNA RBAT1 in improving diagnosis and prognosis of ovarian carcinoma. Issue 1 (6th October 2022) - Luo, Jie; Zhang, Yuqing; Zheng, Ting; Jing, Yongping; Cao, Rongyu; Wu, Minmin; Fan, Die; Tao, Ying; Zhao, Mandan
Abstract : Tumorigenesis of bladder cancer and retinoblastoma is correlated with long non-coding RNA (lncRNA) RBAT1. However, the role of RBAT1 in ovarian carcinoma (OC) is unclear. Thus, the study explored the role of RBAT1 in OC. This research enrolled patients with OC ( n = 68), irritable bowel disease (IBD, n = 68, females), digestive tract inflammation (DTI, n = 68, females), urinary tract infection (UTI, n = 68, females), endometriosis (EM, n = 68, females), and healthy controls (HCs, n = 68) to collect plasma sampled. OC and paired non-tumor tissues were collected from patients with OC. RBAT1 accumulation in all samples was analyzed using RT-qPCR. The role of plasma RBAT1 in OC diagnosis was examined using the ROC curves with OC patients as the true positive cases and other patients and HCs as the true negative cases. The role of RBAT1 in predicting the survival of OC patients was analyzed using the survival curve study. RBAT1 was overexpressed in both OC plasma and tissues. Plasma RBAT1 levels were correlated with RBAT1 levels in OC tissues but not in non-tumor tissues. Plasma RBAT1 could distinguish OC patients from other patients and HCs. Patients with high plasma RBAT1 levels had a shorter survival. RBAT1 is overexpressed in OC and might be applied to improve the diagnosis and prognosis of OC.